REFORMULATION OF GEOMETRIC OPTICS WITHIN THE FRAMEWORK OF ABELIAN U(1) GAUGE THEORY: A NOVEL APPROACH TO UNDERSTANDING LIGHT PROPAGATION - Natalisanto, Adrianus Inu; Purwaningsih, Sri (Universitas Mataram, 2025)
This study introduces a reformulation of geometrical optics through the framework of Abelian U(1) gauge theory. By leveraging this novel approach, phase equations are derived, serving as the cornerstone for determining the trajectories of light rays. The proposed formulation is validated through simulations of light propagation in diverse scenarios, including homogeneous refractive index media, vacuum, anisotropic materials, and optical metamaterials. These results underscore the versatility and predictive power of this gauge-theoretic approach, opening new avenues for exploring and modeling complex optical phenomena.